2017
DOI: 10.3233/jad-170248
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Dietary Patterns, Foods, and Micro- and Macronutrients with Alzheimer’s Disease and Late-Life Cognitive Disorders: A Systematic Review

Abstract: In the last decade, the association between diet and cognitive function or dementia has been largely investigated. In the present article, we systematically reviewed observational studies published in the last three years (2014-2016) on the relationship among dietary factors and late-life cognitive disorders at different levels of investigation (i.e., dietary patterns, foods and food-groups, and dietary micro- and macronutrients), and possible underlying mechanisms of the proposed associations. From the review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
6
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(181 citation statements)
references
References 138 publications
3
164
6
8
Order By: Relevance
“…Dietary patterns are strongly involved in the risk of developing AD and in its course, once the disease has established 111. Diets with patterns similar to Mediterranean and Dietary Approaches to Stop Hypertension diets have been associated with a reduced risk of AD and milder disease course, while Western-style diet represents an important risk factor 111.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary patterns are strongly involved in the risk of developing AD and in its course, once the disease has established 111. Diets with patterns similar to Mediterranean and Dietary Approaches to Stop Hypertension diets have been associated with a reduced risk of AD and milder disease course, while Western-style diet represents an important risk factor 111.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary patterns are strongly involved in the risk of developing AD and in its course, once the disease has established 111. Diets with patterns similar to Mediterranean and Dietary Approaches to Stop Hypertension diets have been associated with a reduced risk of AD and milder disease course, while Western-style diet represents an important risk factor 111. Among nutrients, saturated fatty acid consumption is associated with increased risk of AD, while an adequate dietary intake of polyphenols, unsaturated fatty acids and vitamins A, E and C may have a protective effect against the development of dementia 111,112.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show that coffee consumption may be associated with a lower risk for several neurological disorders, such as Alzheimer's disease (AD) and Parkinson's disease . Several cross‐sectional and longitudinal population‐based studies have suggested a protective effect of coffee use against late‐life cognitive impairment and decline . However, elucidation of the molecular mechanisms for the protective effects of coffee against these neurological disorders have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, effective dietary strategies that can slow down cognitive decline and reduce the incidence of dementia need to be identified. The Mediterranean diet (MedDiet) has been associated with slower cognitive decline and a lower risk of cognitive impairment and dementia in multiple observational studies 1. More recently, first observational analyses have shown that better adherence to the Mediterranean-DASH Intervention for Neurodegenerative Delay (MIND) diet was associated with a slower rate of cognitive decline and reduced incidence of Alzheimer’s disease in US cohorts 2–4…”
Section: Contextmentioning
confidence: 99%